Microwave-assisted chemoselective transamidation of secondary amides by selective N-C(O) bond cleavage under catalyst, additive and solvent-free conditions - Singh V.; Rajput K.; Mishra A.; Singh S.; Srivastava V. (My University, 2025)
A microwave-assisted, highly chemoselective protocol has been developed for the transamidation of tert-butyloxycarbonyl (Boc) activated secondary carboxamides with amines. Under non-conventional microwave techniques, the reactions were achieved under catalyst, additive, promoter and solvent-free conditions. The transamidation of a structurally diverse set of amides and amines was accomplished in good to excellent yields. The salient features of the developed methodology include a simple operation, broad substrate scope, functional group tolerance, practicality, and the scalability. © 2023 The Royal Society of Chemistry.